Rumors of change : essays of five decades - Hassan, Ihab, 1925-2015 (University of Alabama Press, 1995)
"These essays span five decades and mirror American culture in the postwar years. They represent Hassan's various topics, styles, critical methods, and social attitudes. From formalism in the forties to multiculturalism in the nineties, from existential engagements to postmodern dubieties, from Paul Bowles, Jean Stafford, and William Burroughs to Peter Matthiessen, Marge Piercey, and Christina Dodwell, the essays move with the momentum of history. But they move critically. In sympathy with their subjects, they challenge nonetheless the cant and pieties of their moment."--Jacket.